THE RELATIONSHIP BETWEEN KNOWLEDGE LEVEL AND THE INCIDENCE OF SEAFOOD POISONING IN THE ISLAND REGION IN 2020 - Dewi Puspa Rianda; Muthia Deliana; Santa Novita Y S (Bajang Institute, 2021)
Seafood is a term for food in the form of marine animals and plants that are caught, fished, taken from the sea or cultivated. Society is a set of human beings who due to the demands of needs and influence certain beliefs, thoughts, and ambitions are united in collective life. The purpose of this study is to determine the relationship between knowledge levels and the incidence of seafood poisoning in the archipelago in 2020. This study uses a correlational descriptive research design with the approach used is cross sectional. The sampling technique used is Non probability sampling, namely 49 communities in the working area of the Tembeling Health Center, Bintan Regency. Data collection is carried out by distributing questionnaires. Data analysis using Univariate and Bivariate analysis. The results showed that the majority of people had gained knowledge about seafood poisoning as much as 70% and almost some people had never experienced the incidence of seafood poisoning, namely as much as (55%). The results of the bivariate analysis showed that there was a significant relationship between the level of knowledge and the incidence of seafood poisoning = 0.002. The results of this study concluded that the more ever and higher in obtaining public knowledge, the better it will be in preventing the occurrence of seafood poisoning.